R&D Intensity, Intelectual Capital Disclosure and Financial Business Performance: The Role of Foreign Ownership - Bunyamin Bunyamin; Helena Irene Amastasya (PT. Anagata Sembagi Education, 2025)
This research aims to examine and analyse the role of foreign ownership on financial business performance with R&D intensity and intelectual capital disclosure as intervening variables. The research sample was pharmaceutical firms that listing in Indonesia Stock Exchange in 2019-2022; 9 pharmaceutical firms that accomplish the requirements of this research. Data were analysed by using the Structural Equation Modelling/SEM method with SmartPLS program. This research found that intelectual capital disclosure, R&D intensity had a positive effect on ROE. Foreign ownership has no effect on ROE. R&D intensity and foreign ownership have a positive effect on intelectual capital disclosure, foreign ownership has a positive effect on R&D intensity. The limitations of the research are time constraints and single sector studies. In the future, other industries may examine the role of foreign ownership, R&D intensity, and disclosure of intellectual capital on their financial business performance.